Model and Financial Performance: Panel Data in Causality and Cointegration Test - Indrabudiman, Amir (International Journal of Engineering and Technology, 2018)
This paper aims to analyze the interaction between financial performance variables and bankruptcy status of companies in the banking industry in Indonesia. This study used the test of causality and cointegration of panel data for variable bankruptcy status and variable of financial performance among others (variable of NPL, ROA, CAR, NIM, SIZE, GROWTH, LEVERAGE) at 43 banks listed on BEI during 2010-2016 financial reporting period. From the research conducted in the findings that between the status of bankruptcy and variable financial performance of banks in Indonesia are only a few variables that have a two-way relationship, this is seen in the test results of causality lags 1, using lags 5, 10 and 15 this causal relationship is getting smaller . However, cointegration has been confirmed by using lags 1-1 to 1-4 lags interval premises, there are 7 variables that in each cointegrated each other.